SOLIDARITY EXPRESSIONS EMERGED IN ADDRESSING SYSTEM AS LINGUISTIC SIGNAL - Agung, Winantu Kurnianingtyas Sria (Pusat Pengembangan Bahasa IAIN Tulungagung, 2016)
Language has the particular roles relevant to the situation and event when the communication holds. In taking a part into a communication, the speaker must understand in what context they speak whether he speaks in formal or informal context. Moreover, the role-relationship between the speaker and hearer, for instance, the communication between parents to children, a boss and his employee. Then, the setting of the communication, for example, at home, offce, market, etc also becomes the major factors in conducting communication. Language allows community not only to communicate with others but also to establish personal identity among individuals and communities. The social class or social stratifcation exists in the term of power and solidarity. The existence of power and solidarity reï¬ects in the way people communicate with others and it can be seen through thelanguage they use.